2018
DOI: 10.1089/ars.2017.7313
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria, the NLRP3 Inflammasome, and Sirtuins in Type 2 Diabetes: New Therapeutic TargetsReviewing Editors:Markus Bachschmid, Dylan Burger, Vittorio Calabrese, Amadou Camara, Lukas Kubala, Giuseppe Poli, and Chandan K. Sen

Abstract: In this review article, we attempt to provide an overview of the existing literature concerning the crosstalk between mitochondrial impairment and the inflammasome, with particular attention to cellular and mitochondrial redox metabolism and the potential role of the NLRP3 inflammasome and sirtuins in the pathogenesis of type 2 diabetes. In addition, we discuss potential targets for therapeutic intervention based on these molecular interactions. Antioxid. Redox Signal. 29, 749-791.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(28 citation statements)
references
References 397 publications
(415 reference statements)
0
28
0
Order By: Relevance
“…There has been increasing attention on the molecular mechanisms of NLRP3 in a number of diseases. Recent studies have reported significant protective effects resulting from suppression of NLRP3 inflammasome activation in liver fibrosis, systemic sclerosis, systemic lupus erythematosus, systemic sclerosis, diabetes, inflammasome-related eye disease, inflammatory bowel disease, rheumatoid arthritis, and CNS diseases (Zhou et al, 2016;Alegre et al, 2017;Rovira-Llopis et al, 2018;Shen et al, 2018;Yerramothu et al, 2018;Chen et al, 2019a). Meng et al (2019) demonstrated that PPARγ activation exerts an anti-inflammatory effect by suppressing NLRP3 inflammasome activation in spinal cord-derived neurons.…”
Section: Discussionmentioning
confidence: 99%
“…There has been increasing attention on the molecular mechanisms of NLRP3 in a number of diseases. Recent studies have reported significant protective effects resulting from suppression of NLRP3 inflammasome activation in liver fibrosis, systemic sclerosis, systemic lupus erythematosus, systemic sclerosis, diabetes, inflammasome-related eye disease, inflammatory bowel disease, rheumatoid arthritis, and CNS diseases (Zhou et al, 2016;Alegre et al, 2017;Rovira-Llopis et al, 2018;Shen et al, 2018;Yerramothu et al, 2018;Chen et al, 2019a). Meng et al (2019) demonstrated that PPARγ activation exerts an anti-inflammatory effect by suppressing NLRP3 inflammasome activation in spinal cord-derived neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we reveal a new function of M in the activation of the NLRP3 inflammasome and IL-1␤. As a crucial component of the innate immune system, the inflammasome not only plays an important role in host defense against pathogen infections but also is involved in the progression of inflammatory diseases, such as gout and type 2 diabetes (47,48). DENV triggers NLRP3 inflammasome assembly in platelets, and platelets may contribute to increased vascular permeability by regulating IL-1␤ (37).…”
Section: Figmentioning
confidence: 99%
“…Another group of mitochondria-targeted antioxidants includes water-soluble Szeto Schiller (SS) peptides, small cell permeable antioxidants that are selectively and rapidly taken up into the IMM of different types of cells, including renal, embryonic and endothelial cells. It has been shown that they can modulate mitochondrial ROS production and reduce the mitochondrial permeability transition, preventing necrosis and apoptosis, which are promoted by inhibition of the mitochondrial ETC or oxidative stress [144]. Another current strategy under evaluation for mitochondrial targeting is that of liposomes, of interest due to their clearance rates after systemic injection.…”
Section: Microbiota and Mitochondria: Potential Therapeutic Strategiementioning
confidence: 99%
“…Liposomes are self-assembling colloidal structures mainly composed of phosphatidylglycerol, cholesterol and phosphatidylcholine. In addition, several studies suggest that mitochondria-targeting liposomes are able to enhance the drug efficacy in both in vitro and in vivo models by delivering therapeutic moieties to the mitochondria [144].…”
Section: Microbiota and Mitochondria: Potential Therapeutic Strategiementioning
confidence: 99%